The Effect of Job Displacement on Subsequent Health - William T. Gallo; Elizabeth H. Bradley; Stanislav V. Kasl (Vierteljahrshefte zur Wirtschaftsforschung, 2001)
Using data from the 1994-1996 waves of the German Socio-Economic Panel (GSOEP), this prospective longitudinal study investigates the association between job displacement and subsequent self-assessed health (SAH). The sample consists of 253 displaced workers and a comparison group of 6,934 continuously-employed workers. Controlling for baseline SAH and standard demographic characteristics, we find no statistical association between job displacement and subsequent SAH. Our findings are consistent with those of earlier studies of the relationship between unemployment and subsequent health.
Keywords: 330; Kündigung; Arbeitslosigkeit; Gesundheit; Deutschland